Faktor-Faktor Yang Mempengaruhi Kesehatan Waktu Pelaporan Keuangan Pada Perusahaan Costumer Goods - Gibran Ramadhan; Dwi Puji Rahayu; Bambang Suroso; Indrian Supheni; Wina Aprilia Purnamasari (Jurnal Literasi Akuntansi, 2023)
In this study, the researcher aimed at analyzing the effectt of profitabilityy, capitall structuree and leveragee on the capitall structuree off the mining sektor listed on the Indonesiaa Stockk Exchangee (IDX) for the 2016-2019 period.The research method used is a quantitative approach by involving 54 companies. The samplingg techniquee usedd is purposivee samplingg obtainedd a samplee off 28 companiess that meet the criteria. Data were analyzed according to defined operational definitions